Dividen nnouncement Effects On stock returns:a Test of The Signaling Hypothesis in the Indinesian Stock Market - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The signaling hypothesis assert that managers use divedend announcements to signal changes in their expectation about the future prospects of the firms.The result of the study tend to support the proposition that market participants make considerable use of the information implicit in divident announcements.The market reacts positivily to these announcements when cash dividends are increased.Whereas, themarket responds negatively when dividend is reduced or when a stock dividend distribution takes place.The study finds little evidence to support the view that changes in cash dividends and stock dividends provide incremental information on a firm's future earnings performance.On the other hand, the study notes significant earning changes in the year prior to dividend announcements.